Gold‐nanoparticle‐decorated thermoplastic polyurethane electrospun fibers prepared through a chitosan linkage for catalytic applications. Issue 1 (2nd September 2016) - Cheng, Hui‐Hui; Chen, Fang; Yu, Jian; Guo, Zhao‐Xia
ABSTRACT: Thermoplastic polyurethane (TPU)‐electrospun‐fiber‐mat‐supported gold catalysts were prepared by the adsorption of gold nanoparticles (AuNPs) onto a TPU electrospun fiber mat after functionalization with chitosan (CS) by a dip‐coating method. The mechanism for the adsorption of AuNPs was electrostatic interaction between the positive charge of CS (N H 3 + ) and the negative charge of the AuNP surface (COO − ) and coordination between the amine groups of CS and gold. The mat was crosslinked with glutaraldehyde vapor to strengthen the adhesion between the CS coating and TPU fibers after the adsorption of AuNPs. The catalytic activity of the supported gold catalyst was evaluated with the reduction of 4‐nitrophenol by NaBH4 to demonstrate the excellent catalytic performance and its reusability for at least 10 cycles without a loss in activity. The rate constant increased with both an increase in the amount of supported catalyst and an increase in the ratio of the mat surface area to AuNP within the investigated scope. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44336. Abstract :